Barriers and enablers to the sharing of human rights policies through South-South cooperation - Morais de Sa e Silva, Michelle (CLACSO, 2021)
The practice of South-South Cooperation for the purpose of policy transfer has achieved great political interest and priority in recent years. However, some public policies have had greater success than others in getting transferred across countries of the geopolitical South. In this framework, this research project has looked into why participatory and rights-based policies in Brazil, especially the policy on education for human rights, have not diffused internationally despite governmental efforts. Five cases were compared where Brazil cooperated with Haiti, Cuba, El Salvador and Guinea Bissau.